Case report: Unruptured small middle cerebral artery aneurysm with perianeurysmal edema - Goto, Yoshihiro; Morofuji, Yoichi; Shiozaki, Eri; Uchida, Daiki; Kawahara, Ichiro; Ono, Tomonori; Haraguchi, Wataru; Tsutsumi, Keisuke (Frontiers in Surgery, 2023)
Background: Perianeurysmal edema (PAE) has a tendency to occur in embolized aneurysms but also in partially thrombosed, large, or giant aneurysms. However, there are only a few cases recorded in which PAE was detected in untreated or small aneurysms. We suspected that PAE might be an impending sign of aneurysm rupture in these cases. Herein, we presented a unique case of PAE that was related to an unruptured small middle cerebral artery aneurysm. Case description: A 61-year-old woman was referred to our institute due to a newly formed abnormal fluid-attenuated inversion recovery (FLAIR) hyperintense lesion in the right medial temporal cortex. Upon admission, the patient did not present with any symptoms or complaints; however, FLAIR and CT angiography (CTA) suggested an increased risk of aneurysm rupture. Aneurysm clipping was conducted, and no evidence of subarachnoid hemorrhage and hemosiderin deposits around the aneurysm and brain parenchyma was noted. The patient was discharged home without any neurological symptoms. MRI taken at eight months post-clipping revealed complete regression of the FLAIR hyperintense lesion around the aneurysm. Conclusion: PAE in unruptured, small aneurysm is thought to be an impending sign of aneurysm rupture. Early surgical intervention is critical even for small aneurysms with PAE.